Epigenetic diversity increases the productivity and stability of plant populations - Latzel, Vít; Allan, Eric; Bortolini Silveira, Amanda; Colot, Vincent; Fischer, Markus; Bossdorf, Oliver (Nature communications, 2013)
Biological diversity within species can be an important driver of population and ecosystem functioning. Until now, such within-species diversity effects have been attributed to underlying variation in DNA sequence. However, within-species differences, and thus potentially functional biodiversity, can also be created by epigenetic variation. Here, we show that epigenetic diversity increases the productivity and stability of plant populations. Epigenetically diverse populations of Arabidopsis thaliana produce up to 40% more biomass than epigenetically uniform populations. The positive epigenetic diversity effects are strongest when populations are grown together with competitors and infected with pathogens, and they seem to be partly driven by complementarity among epigenotypes. Our study has two implications: first, we may need to re-evaluate previous within-species diversity studies where some effects could reflect epigenetic diversity; second, we need to incorporate epigenetics into basic ecological research, by quantifying natural epigenetic diversity and testing for its ecological consequences across many different species.
Keywords: Biodiversity; Senecio; Plant Diseases; Polymorphism, Genetic; Plant Weeds; plevel; Epigenesis, Genetic; ekosystém; epigeneze genetická; Ecosystem; polymorfismus genetický; biodiverzita; Pseudomonas syringae; Arabidopsis; nemoci rostlin